Alternatif Teknik Rehabilitasi Lahan Terdegradasi pada Lahan Bekas Galian Industri sekitar Tambang di Kabupaten Magelang, Jawa Tengah - Yusuf, Gusman; Wijaya, Nely (ReTII, 2019)
Government efforts in order to cope with the increase in the extent of critical land, is the occurrence of changes in environmental baseline caused by natural and human behavior. The process of repairing degraded land in Indonesia is one of the efforts to reforest and cope with natural disasters, such as landslides. One of the activities that results in the criticality of an area is open mining which is not followed by immediate efforts to optimize reclamation. To rehabilitate degraded land used as industrial excavation land, it is necessary to choose the types of soil fertilizers that are able to grow in the open and contain nutrients and contain chemicals that are toxic to plants. After that careful efforts were made in implementing soil improvement. The form of repairs carried out by mixing limestone and chemicals.